2020
DOI: 10.1039/d0ma00546k
|View full text |Cite
|
Sign up to set email alerts
|

Superior anchoring effect of a Cu-benzenehexathial MOF as an aluminium–sulfur battery cathode host

Abstract: A Cu-BHT MOF as a suitable cathode host for aluminium–sulfur batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 81 publications
3
28
0
Order By: Relevance
“…, the E b values of S 8 *, Al 2 S 18 *, Al 2 S 12 *, Al 2 S 6 *, and Al 2 S 3 * were −1.81, −2.18, −1.22, −4.18, and −2.97 eV, respectively, in the range of −1.81 to −4.18 eV. A previous study demonstrated that the E b values of S 8 and Al 2 S n species on Cu-BHT MOF were in the range of −1.11 to −3.56 eV and −0.76 to −0.87 eV for the graphene structure 23. This indicated that Ag@Ti 3 C 2 O 2, as a sulfur host, had the ability to adsorb S 8 and Al 2 S n species.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…, the E b values of S 8 *, Al 2 S 18 *, Al 2 S 12 *, Al 2 S 6 *, and Al 2 S 3 * were −1.81, −2.18, −1.22, −4.18, and −2.97 eV, respectively, in the range of −1.81 to −4.18 eV. A previous study demonstrated that the E b values of S 8 and Al 2 S n species on Cu-BHT MOF were in the range of −1.11 to −3.56 eV and −0.76 to −0.87 eV for the graphene structure 23. This indicated that Ag@Ti 3 C 2 O 2, as a sulfur host, had the ability to adsorb S 8 and Al 2 S n species.…”
mentioning
confidence: 88%
“…16−22 Inspired by this, Bhauriyal et al studied the binding strength between Al 2 S n and Cu-benzeneheaxthial (Cu-BHT) MOF by using DFT calculations, suggesting that Cu-BHT MOF could be used as a promising sulfur host for Al−S batteries. 23 However, the interaction mechanism and Al 2 S n conversion remain unclear. First, the main evaluation of sulfur hosts is the binding strength (adsorption energy), and it is generally believed that the stronger the binding is, the better.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 225 ] Due to price fluctuations and constraints in the supply of cobalt, the momentum of using electric vehicles and grid‐storage applications has come to a standstill which has prompted the researchers to seek alternative cost‐efficient metals. [ 226,227 ] As a result, Bhauriyal et al [ 228 ] employed “a 2D Cu‐benzenehexathial (Cu‐BHT) MOF (Figure 11f)” as a potential anchoring host for S‐cathode in Al/S battery. The conductive nature of Cu‐BHT‐MOF could successfully compensate for the intrinsic insulating nature of sulfur‐based products.…”
Section: Progress Toward Cathode System In a Metal–sulfur Interacted ...mentioning
confidence: 99%
“…h) Illustration of uniform Al 2 S 3 layer deposition on the Cu-BHT monolayer surface. Reproduced with permission [228]. Copyright 2020, Royal Society of Chemistry.…”
mentioning
confidence: 99%